10.8% Efficiency Polymer Solar Cells Based on PTB7‐Th and PC71BM via Binary Solvent Additives Treatment. (19th July 2016) - Wan, Qun; Guo, Xia; Wang, Zaiyu; Li, Wanbin; Guo, Bing; Ma, Wei; Zhang, Maojie; Li, Yongfang
Abstract : In this work, polymer solar cells are fabricated based on the blend of PTB7‐Th: PC71 BM by using a mixed solvent additive of 1, 8‐diiodooctane and N ‐methyl pyrrolidone to optimize the morphology of the blend. A high power conversion efficiency (PCE) of 10.8% has been achieved with a simple conventional device. In order to deeply investigate the influence of the mixed solvent additives on the morphology and device performance, the variations of the molecular packing and bulk morphology of the blend film cast from ortho‐dichlorobenzene with single or binary solvent additives are measured. Although all the blend films exhibit similar domain size and nanoscale phase separation, the blend film processed with mixed solvent additive shows the highest domain purity, resulting in the least bimolecular recombination, relatively high J sc and FF, and hence enhanced PCE. Therefore, the best photovoltaic performance with the V oc of 0.82 V, J sc of 19.1 mA cm −2, FF of 69.1%, and PCE of 10.8% are obtained for the device based on the blend with binary solvent additive treatment. Abstract : For the PTB7‐Th:PC71 BM blend system, the binary solvent additives of 1, 8‐diiodooctane and N ‐methyl pyrrolidone are used to enhance the domain purity, so that a power conversion efficiency of 10.8% is achieved with the conventional device structure, which is much higher than that of the devices without or with single solvent additive treatment.